Contribution of edible insects to improved food and nutrition security: A review. (30th January 2022) - Matiza Ruzengwe, Faith; Nyarugwe, Shingai P.; Manditsera, Faith A.; Mubaiwa, Juliet; Cottin, Sarah; Matsungo, Tonderayi M.; Chopera, Prosper; Ranawana, Viren; Fiore, Alberto; Macheka, Lesley
SUMMARY: The consumption of insects "entomophagy" or insect‐based foods is increasingly being recognised as an emerging solution to promote diet diversification and address the multiple burden of malnutrition. Although several studies suggest edible insects as valuable nutrient sources, few have evaluated the effects of processing on nutrient bioavailability and bioaccessibility and provided actual evidence on human nutrition. Moreover, there is limited evidence of their actual contribution to improved food and nutrition security. Therefore, the review evaluated existing evidence on human interventions and the effects of processing methods on bioavailability and bioaccessibility of key nutrients since these directly influence food and nutrition security outcomes. Seven human efficacy studies have been conducted to date and these show limited observable effects on nutrition status therefore more research is required. Findings also suggest that the processing method, insect matrix, composition of the food matrix and interaction with other food components can influence nutrient bioavailability and bioaccessibility. Hence, these should be considered during formulation and upscaling for entomophagy and insect‐based foods to be viable intervention strategies against malnutrition. Abstract : Edible insects and edible‐insect based products are a potential intervention strategy against malnutrition. Processing of these edible insects influences their nutrient quality hence affecting their use as a food‐based strategy.